Optimization of Chemicaly Activated Candlenut and Walnut Shell Biosorbents for Produced Water Purification Within an Iot-Based Monitoring System - Muhammad Khairul Afdhol; Rika Lala Saputri; Mursyidah; Fiki Hidayat; Tomi Erfando; Ari Prasetyo; Adiella Zakky Juneid (Scientific Contributions Oil and Gas, 2026)
Produced water from petroleum operations contains high levels of hydrocarbons, suspended solids, and dissolved contaminants that must be treated before discharge or reuse. This study aims to optimize biosorbents derived from candlenut and walnut shells through chemical activation using potassium hydroxide (KOH) for the purification of produced water. In addition, an Internet of Things (IoT)-based monitoring system was integrated to enable real-time assessment of water quality parameters. The biosorbents were characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) to identify surface functional groups and morphological modifications. Experimental evaluations of turbidity, bulk density, and total dissolved solids (TDS) were conducted under various operating conditions. The activated biosorbents exhibited enhanced hydroxyl and carboxyl functional groups, as confirmed by FTIR, with an optimal bulk density of 0.76 g/cm³. Under optimum conditions (pH 7, contact time 90 min, adsorbent dosage 15 g/L), turbidity and TDS removals reached 80% and 75%, respectively. The IoT system successfully enabled real-time data acquisition and process monitoring, ensuring operational reliability. The maximum adsorption capacity based on the Langmuir model reached 33.8 mg/g for KOH-activated walnut and 31.2 mg/g for candlenut biosorbent. Overall, the chemically activated candlenut and walnut biosorbents demonstrated excellent adsorption capacity and potential for sustainable produced water treatment. This approach offers an environmentally friendly and cost-effective solution by utilizing local biomass waste integrated with modern IoT-based control technologies. Adsorption behavior was further evaluated using Langmuir/Freundlich isotherm and kinetic models.